'FREEDOM FROM HATRED': THE ROLE OF KHANTI IN COMPLEMENTING THE WORK OF INTERNATIONAL HUMANITARIAN LAW (IHL). Issue 1 (3rd July 2021) - Wakefield, Alex
ABSTRACT: This article explores the Buddhist quality of khanti . Khanti/kṣānti translates as patience, forbearance or tolerance, and includes the notions of non-retaliation and forgiveness. Understood in Buddhist texts as the opposite of anger and hatred, khanti may support measures of international humanitarian law (IHL) which prevent unlawful reprisals and other atrocities motivated by revenge in the context of war. As with IHL, Buddhism emphasises common humanity through the recognition of universal suffering. By drawing on Buddhist narratives and treatises, which apply the analysis of non-self (anattā) to anger itself as a basis for khanti, this article demonstrates that khanti is regarded as particularly appropriate for dealing with conflict. Khanti addresses the immediate psychological responses of victims of violence during conflict, thus offering immediate relief of suffering and preventing its further escalation. This article suggests that the brahmavihārā s, particularly loving-kindness ( mettā ), may practically develop the quality of khanti . Just as mindfulness meditations have been used in the secular and global contexts, so too mettā practice as the development of khanti could be utilised alongside military training and the work of the International Committee of the Red Cross to enhance compliance with IHL.